Three Sufi Communities Guarding the Earth: A Case Study of Mitigation and Adaptation to Climate Change in Indonesia - Maghfur Ahmad (Al-Jami'ah: Journal of Islamic Studies, 2019)
Prasenjet Duara (2015) accuses divine religions as the cause of the environmental crisis and natural disasters. Duara's thesis was counterattacked by scientists and religionists who stated that religion has the spirit and teachings of careness for the environment. Nevertheless, the arguments they built are still theological, normative and theoretical. This study is an antithesis to the Duara’s statement and at the same time presents evidence based on the primary data that occurred in three Sufi communities. The focus of this study analyzes Sufi activism in Indonesia in safeguarding the earth, as a form of substantial religious responses to the environmental crisis due to climate change. Through the principles and mechanism of qualitative research methods, researchers sought to analyze mitigation and adaptation actions to climate change carried out by the Majlis Zikir Kraton Pekalongan, Jamaah Aoulia Panggang and Pesan Trend Ilmu Giri. The data are obtained through interviews, observation and documentation and they are analyzed interactively. The results of the study revealed that climate change is believed by the Sufis as God’s authority due to human destructive behavior. For Sufis, overcoming climate change must begin with a change in the perspective of human relations, nature and God. In the case of three Sufi communities, religion is not just a doctrine of the relationship between God and humans, but also operational guidance on how to synergize with nature. Through a substantial religious spirit, the Sufis guard the earth through the re-actualization of the narratives of takhalli, tahalli and tajalli, as ecological repentance, ecological movements, and ecological campaigns in mitigating and adapting to climate change. [Prasenjet Duara (2015) menuduh agama-agama samawi sebagai penyebab terjadinya krisis lingkungan dan bencana alam. Tesis Duara mendapat serangan balik dari ilmuwan dan agamawan yang menyatakan bahwa agama memiliki spirit dan ajaran kepedulian terhadap lingkungan. Hanya saja argumen yang mereka bangun masih bersifat teologis, normatif dan teoritis. Kajian ini merupakan antitesa terhadap pernyataan Duara, dan sekaligus menyajikan bukti berdasarkan data-data lapangan  yang terjadi pada tiga komunitas sufi. Fokus kajian ini menganalisis aktivisme kaum sufi di Indonesia dalam menjaga bumi, sebagai bentuk respons kaum beragama subtansial terhadap krisis lingkungan akibat perubahan iklim.  Melalui prinsip dan mekanisme metode penelitian kualitatif, peneliti berusaha menganalisis tindakan mitigasi dan adaptasi terhadap perubahan iklim yang dilakukan oleh Majelis Zikir Kraton Pekalongan, Jamaah Aoulia Panggang dan Pesan Trend Ilmu Giri Yogyakarta. Data-data diperoleh melalui wawancara, observasi dan dokumentasi dan dianalisis secara interaktif. Hasil kajian mengungkap bahwa perubahan iklim diyakini oleh kaum sufi sebagai otoritas Tuhan yang disebabkan perilaku destruktif manusia. Bagi kaum sufi, mengatasi perubahan iklim harus dimulai dari perubahan cara pandang relasi manusia, alam dan Tuhan. Dalam kasus di tiga komunitas sufi, agama tidak sekedar menjadi doktrin tentang relasi Tuhan dan manusia, melainkan juga petunjuk operasional bagaimana bersinergi dengan alam. Melalui spirit agama yang subtansial, kaum sufi menjaga bumi melalui reaktualisasi narasi takhalli, tahalli dan tajalli, sebagai pertaubatan ekologi, gerakan ekologi, serta kampanye ekologi dalam perilaku mitigasi dan adaptasi terhadap perubahan iklim.]